A capacitor based fast I-V characteristics tester for photovoltaic arrays. (July 2018) - Chen, Zhicong; Lin, Wencheng; Wu, Lijun; Long, Chao; Lin, Peijie; Cheng, Shuying
Abstract: In order to efficiently evaluate the operating status of photovoltaic (PV) arrays, a design of fast current-voltage (I-V) characteristic tester is proposed in this paper. The tester uses the dynamic capacitor charging method to quickly sweep I-V characteristic curves. Then, a new artificial bee colony and Nelder-Mead simplex (ABC-NMS) hybrid algorithm is used to extract parameters of the single diode model of PV arrays. The experimental results show that the tester can quickly measure high-quality I-V curves of PV array and achieve accurate model parameters extraction. In addition, the root mean square error (RMSE) of curve fitting can be used to effectively indicate the partial shading condition.